Collective Intellectual Property in Michoacán: Negotiating Economic and Cultural Agendas in the Artisanal Field - Lucero Ibarra Rojas (Oñati Socio-Legal Series)
The state of Michoacán, México, has almost 50 collective trademarks registered for artisanal products, which were created by initiative of different state institutions. This article aims to understand the different influences that are mediated by law when collective forms of intellectual property are incorporated and negotiated by different institutions with different aims within the realm of the state. By looking closely at the experience in Michoacán, I argue that two economic/cultural agendas can be identified. On the one hand, there is the federal agenda that aims for a national and international projection of a Mexican product, focused on the successfully industrialized national products closely linked with México's imagery for a foreign audience. On the other hand, there are the expectations of Michoacán's local government, which are strongly related with a pluralist discourse and with the different policy approaches it inspires. Between the two, the country’s cultural agenda becomes shaped by economic concerns that are, in turn, defined by the worldviews of state institution's agents.